Rancangan Ask Me Studi Kasus Kopma UNY di Era Pandemi Covid-19: Mewujudkan Ekonomi Sejahtera Tahun 2045 - Akmal Firmansyah; Anisyya Nur Kasanah; Navyandra Kartika Sari (EXERO : Journal of Research in Business and Economics, 2022)
During the Covid-19 pandemic that hit the world, all activities were transformed using digital. This is because of restrictions on gathering in one place or commonly known as social distancing. The activities of buying and selling transactions that are usually carried out at the Student Cooperative (KOPMA) have also undergone changes and the economic sector has been hit by a wave of economic recession from the impact of this pandemic. Our alternative solution is to design a Smart Cooperative Application to Improve the Economy (ASK ME) which can be useful for media transactions at the Yogyakarta State University Student Cooperative, as well as to increase the turnover of Yogyakarta State University Student Cooperatives in particular, and also help improve the economy of the MSMEs around Special Region of Yogyakarta and Indonesia. This scientific paper aims to design and develop an innovation in the form of an application, which can be used for transactions, so that it becomes a place for buying and selling, as well as a forum for bringing together existing MSMEs to develop their business. The supporting basis for conducting this research is Law Number 17 of 2012 concerning Cooperatives, and Article 33 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely that the Indonesian economy is structured as a joint effort based on the family principle. This study will describe the urgency of the formation of a Smart Cooperative Application to Improve the Economy (ASK ME). The method in writing this scientific paper uses the Research and Development (RD) method, namely conducting research on the urgency of making a Smart Cooperative Application to Improve the Economy (ASK ME) and then developing a Smart Cooperative Application to Improve the Economy (ASK ME). The research subjects or resource persons are administrators and members, as well as visitors to the Yogyakarta State University Student Cooperative (KOPMA), using data collection techniques in the form of observation, questionnaires or questionnaires and literature study literacy. The data analysis that will be used is qualitative analysis with a descriptive approach and for quantitative analysis of the test results using the Sign Test analysis technique. The research and writing of scientific papers is very important and has an impact, because of the urgency of the Smart Cooperatives Improve the Economy (ASK ME) application design, which must be immediately formed to increase KOPMA turnover and improve the Indonesian economy amidst the covid-19 pandemic.